Readiness of regulation and cybercrime mitigation in syirkah-based securities crowdfunding for MSMEs acceleration - Putri Ruby Kohinoor; Devi Triananda Surya Putri; Anisa Nur Fatimah Karmun (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This study addresses the urgent need for a robust legal and technical framework to support the acceleration of Micro, Small, and Medium Enterprises (MSMEs) through syirkah-based Securities Crowdfunding (SCF) in Indonesia. The modern economy's increasing reliance on information technology has created a new landscape for financial services, but this digitalization also introduces significant cyber risks that threaten the integrity and security of both investors and MSMEs. We analyzed common cyber threats such as phishing, ransomware, and social engineering to identify key vulnerabilities within the SCF ecosystem. Methods: This article employs a comprehensive literature review to analyze the theoretical components of legal readiness and cybersecurity mitigation. The research procedure involved a systematic evaluation of various legal documents, academic literature, and official reports from government and cybersecurity agencies. Findings: The findings indicate that while Indonesia has established a foundational legal umbrella for Sharia SCF, the current regulatory framework remains general and normative, lacking detailed provisions on crucial technical aspects like dispute resolution mechanisms and optimal investor protection. Furthermore, cyber threats pose a significant risk, as evidenced by a substantial number of cyber traffic anomalies in Indonesia's cyberspace. These threats are not merely technical but also ethical, directly conflicting with the Islamic principles of amanah (trust) and justice. Conclusion: This study concludes that a significant gap exists between the general legal framework and the detailed technical requirements needed to ensure security and trust in the digital era. Novelty/Originality of this article: The novelty of this research lies in its integrated approach, which combines an analysis of the legal and regulatory gaps with a comprehensive review of cybercrime threats, and frames both issues within the ethical principles of Islamic law. It also highlights the lack of research on cyber threats targeting the Linux operating system, particularly within the Indonesian fintech sector.